Antireflection film and molded article using the same

The reflection film with a hard coat and low-buckling layer, using urethane acrylate and other components, addresses micro-cracking and whitening issues, providing enhanced durability and anti-reflection properties for molding applications.

JP2025011388APending Publication Date: 2025-01-24AICA KOGYO CO LTD

Patent Information

Application Number
JP2023113474
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-11
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing reflection films used in molding applications suffer from limitations such as micro-cracking on curved surfaces, restricted processing shapes, insufficient anti-reflection characteristics, and susceptibility to whitening during extension, necessitating improved wear resistance and molding compatibility.

Method used

A reflection film comprising a hard coat layer and a low-buckling layer, utilizing urethane acrylate, hollow silica, alumina micro-particles, and a low-refractive index resin composition, with specific weight percentages and particle sizes to enhance durability and anti-reflection properties.

Benefits of technology

The film achieves improved anti-reflection characteristics, high durability, and resistance to whitening during extension, making it suitable for in-mold and out-mold molding applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025011388000001
    Figure 2025011388000001
  • Figure 2025011388000002
    Figure 2025011388000002
  • Figure 2025011388000003
    Figure 2025011388000003
Patent Text Reader

Abstract

To provide an antireflection film that has a good antireflection characteristic, and which is good for molding due to its high fracture elongation, hardly whitened when elongated, and suitable for in-mold molding and out-mold molding, and a molded article using the antireflection film.SOLUTION: Provided is an antireflection film in which a hard coat layer and a low refractive index layer are laminated on a light-permeable base film in the order stated, and the low refractive index layer is a cured substance of a low refractive index resin composition containing urethane (meth)acrylate, a hollow silica, an alumina particulate, a surface additive, and a photoinitiator. The urethane (meth)acrylate contains urethane acrylate that has a structure in which diisocyanate reacted with ethylene glycol and isophorone diisocyanate is further reacted with pentaerythritol triacrylate, and 9 or less functional urethane (meth)acrylate.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an antireflection film in which a hard coat layer and a low refractive index layer are laminated, and to a molded article molded using the same. [Background technology]

[0002] Acrylic photocurable resins are used in many fields to impart special properties to the surfaces of plastic films and plastic molded products. For example, hard coat films, which are applied to PET (polyethylene terephthalate) films to impart high hardness, are used in large quantities as films for touch panels and molding films.

[0003] Among these, insert films are well known for use in molding, in which a pattern is printed on the film surface, and then the film is softened by heating and molded in three dimensions. However, if the hard coat resin layer applied to the film is hardened, microcracks are likely to occur on the curved surface when the film is processed into a three-dimensional shape, and there are limitations on the shape that can be processed. For this reason, the applicant has invented a hard coat agent containing a triazine ring-containing (meth)acrylate prepolymer and organic fine particles with an average primary particle size of 80 to 500 nm as a hard coat resin for insert molding that achieves both surface hardness and moldability (Patent Document 1). This hard coat agent has a film thickness of 1 to 10 μm and is excellent in that it can achieve both sufficient flexibility and surface physical properties.

[0004] By selecting a hard coat agent suitable for such molding applications, the constraints on processing have been alleviated to some extent, but in recent years, there have been cases where anti-reflection properties are also required. As a film having anti-reflection properties, for example, a configuration in which an anti-reflection layer with a low refractive index is formed on a hard coat layer (or a high refractive index layer) is known. When such an anti-reflection film is used as a molding film, the stretchability of the anti-reflection layer is insufficient, and the film may whiten during molding. Therefore, there is room for improvement in order to create an anti-reflection film that has good anti-reflection properties, as well as abrasion resistance and moldability, and is less likely to whiten even when stretched. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 4848200 Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide an antireflection film that has good antireflection properties, high breaking elongation, good formability, and is resistant to whitening even when stretched, and is suitable for in-mold molding, out-mold molding, and the like, and a molded product using the same. [Means for solving the problem]

[0007] In order to solve the above-mentioned problems, the invention of claim 1 provides an antireflection film comprising a hard coat layer and a low refractive index layer laminated in this order on a light-transmitting base film, the low refractive index layer being a cured product of a low refractive index resin composition containing a urethane (meth)acrylate (A), hollow silica (B), alumina fine particles (C), a surface conditioner (D), and a photopolymerization initiator (E), wherein the (A) contains a urethane acrylate (a1) having a structure obtained by reacting ethylene glycol with isophorone diisocyanate, and further reacting pentaerythritol triacrylate with the diisocyanate, and a urethane (meth)acrylate (a2) having 9 or less functionalities (excluding (a1)).

[0008] A second aspect of the present invention provides the anti-reflection film according to the first aspect, wherein the blending amount of the (D) is 20 to 45% by weight based on the total solid content of the composition.

[0009] The invention of claim 3 provides the antireflection film according to claim 1, characterized in that the blending ratio of (a1) in (A) is 15 to 35% by weight based on the total solid content of (A).

[0010] The invention of claim 4 provides the antireflection film according to any one of claims 1 to 3, which is a film for molding.

[0011] The fifth aspect of the present invention provides a molded product produced by using the anti-reflection film according to the fourth aspect of the present invention. Effect of the Invention

[0012] The antireflection film of the present invention has good antireflection properties, high breaking elongation and good formability, and is resistant to whitening even when stretched, and is therefore useful as a molding film suitable for in-mold molding, out-mold molding, and the like. BEST MODE FOR CARRYING OUT THEINVENTION

[0013] The anti-reflection film of the present invention comprises a hard coat layer (hereinafter referred to as HC layer) and a low refractive index layer (hereinafter referred to as low refractive index layer) laminated in this order on a substrate film, and the low refractive index layer is a cured product of a low refractive index resin composition (hereinafter referred to as low refractive index resin) containing urethane (meth)acrylate (A), hollow silica (B), alumina fine particles (C), and a photopolymerization initiator (E). In this specification, (meth)acrylate includes both acrylate and methacrylate.

[0014] The urethane (meth)acrylate (A) used in the present invention includes at least two types of urethane acrylate (a1) having a structure in which a diisocyanate obtained by reacting ethylene glycol with isophorone diisocyanate (hereinafter referred to as IPDI) is further reacted with pentaerythritol triacrylate (hereinafter referred to as PETA), and a urethane (meth)acrylate (a2) having 9 or less functionalities (excluding (a1)).

[0015] (a1) used in the present invention is blended for the purpose of improving the stretchability of the low bending layer. IPDI, an alicyclic diisocyanate used in the synthesis of (a1), is non-yellowing, has excellent weather resistance stability, and at the same time has high rigidity, which can increase the hardness of the cured product. In addition, by reacting it with ethylene glycol, which has a very short carbon chain, it is possible to increase the concentration of urethane bonds in the molecule, and form a main skeleton with a straight chain structure that is highly rigid and has excellent chemical resistance.

[0016] The synthesis method of (a1) is not particularly limited, and a known method can be used. The reaction may be performed without a solvent, but since stirring may become difficult as the molecular weight of (a1) increases, ketones such as MEK, aromatic inactive solvents such as xylene, etc. may be used. In addition, it is preferable to use a catalyst for the reaction between the hydroxyl groups of ethylene glycol and PETA and the isocyanate groups. Examples of such a catalyst include tin-based catalysts such as dibutyltin dilaurate, and metal alkoxide-based catalysts such as cobalt naphthenate. The reaction temperature can be appropriately set, but is preferably 40 to 120°C, more preferably 60 to 100°C.

[0017] The weight average molecular weight (hereinafter referred to as Mw) of (a1) is preferably 1,500 to 30,000, more preferably 2,000 to 15,000, and particularly preferably 3,000 to 10,000. By making it 1,500 or more, sufficient stretchability can be ensured, and by making it 30,000 or less, sufficient abrasion resistance can be ensured, and it is easy to adjust the viscosity to be good for workability. The Mw of (a1) can be adjusted by the molar ratio of ethylene glycol and IPDI to be reacted, and Mw tends to increase when the molar ratio of IPDI to ethylene glycol is made closer. Note that Mw was measured and calculated by gel permeation chromatography using a column using a styrene-divinylbenzene-based packing material and a tetrahydrofuran eluent as the molecular weight in terms of standard polystyrene.

[0018] The amount of (a1) in the low bending strength resin is preferably 3 to 15% by weight, more preferably 5 to 10% by weight, based on the total solid content. By making it 3% by weight or more, sufficient stretchability can be ensured, and by making it 15% by weight or less, sufficient abrasion resistance can be ensured. The amount of (a1) in (A) is preferably 15 to 35% by weight, more preferably 18 to 30% by weight, based on the total solid content of (A).

[0019] (a2) used in the present invention is blended for the purpose of improving the abrasion resistance of the low bending layer. The number of functional groups is 9 or less, and preferably 4 to 9. If the functionality exceeds 9, the crosslinking density increases too much, and there is a tendency for whitening to occur during stretching. In addition, when an acrylic monomer is used instead of a urethane (meth)acrylate, there is also a tendency for whitening to occur during stretching.

[0020] The (a2) can be obtained, for example, by reacting a urethane prepolymer obtained by reacting a polyol with an excess of polyisocyanate with a (meth)acrylate having a hydroxyl group, or by reacting a polyisocyanate with a (meth)acrylate having a hydroxyl group. Among these, urethane (meth)acrylate obtained by reacting a polyisocyanate with a (meth)acrylate having a hydroxyl group is preferred, since it can have a relatively small Mw and can improve abrasion resistance without reducing moldability. There is no particular restriction on the synthesis method of (a2), and a known method can be used, similar to (a1).

[0021] The polyisocyanate used in the synthesis of (a2) includes hexamethylene diisocyanate (hereinafter referred to as HDI), IPDI, diphenylmethane diisocyanate, tolylene diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, hydrogenated xylylene diisocyanate, methylcyclohexylene diisocyanate, HDI isocyanurate, IPDI isocyanurate, etc., which may be used alone or in combination of two or more. Among these, aliphatic and alicyclic diisocyanates that are highly weather resistant and resistant to yellowing are preferred, and among these, HDI, which has high extensibility, IPDI, which has high rigidity, and their trimers, which are isocyanurates, are particularly preferred.

[0022] Examples of the (meth)acrylate having a hydroxyl group used in the synthesis of (a2) include monofunctional (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, bifunctional (meth)acrylates such as glycerin di(meth)acrylate, trifunctional (meth)acrylates such as pentaerythritol tri(meth)acrylate, and tetrafunctional (meth)acrylates such as dipentaerythritol tetra(meth)acrylate, which can be used alone or in combination of two kinds. Among these, bifunctional to trifunctional ones are preferred because they have high reactivity and the film is less likely to whiten when stretched, and PETA is particularly preferred because it has good reactivity and can provide a film with high hardness.

[0023] The amount of (a2) in the low refractive index resin is preferably 10 to 25% by weight, more preferably 15 to 23% by weight, based on the total solid content. By making it 10% by weight or more, sufficient abrasion resistance can be ensured, and by making it 25% by weight or less, sufficient stretchability can be ensured. The amount of (A) including (a1) and (a2) is preferably 20 to 45% by weight, more preferably 25 to 40% by weight, based on the total solid content of the low refractive index resin. By making it 20% by weight or more, sufficient moldability can be ensured, and by making it 45% by weight or less, sufficient low reflection characteristics and abrasion resistance can be ensured.

[0024] The hollow nanosilica (B) used in the present invention is a silica particle having a function of lowering the refractive index of the low refractive index layer while maintaining the coating strength of the layer, and has cavities therein containing air with a refractive index of 1. While the refractive index of solid silica particles is about 1.45, the refractive index of (B) decreases as the occupancy rate of the internal cavities increases, and is about 1.20 to 1.40.

[0025] The primary particle size of (B) is preferably 5 to 150 nm, more preferably 10 to 100 nm, and particularly preferably 40 to 80 nm. By setting it in this range, good dispersibility can be obtained without impairing the transparency of the low refractive index layer. In particular, if it is 40 to 80 nm, the occupancy rate of the cavity can be increased to lower the refractive index while ensuring a thickness of the outer shell that does not cause a lack of strength. An example of a commercially available product is Sururia 4320 (trade name: manufactured by JGC Catalysts and Chemicals, primary average particle size 60 nm).

[0026] The amount of (B) in the low refractive index resin is preferably 15 to 35% by weight, more preferably 20 to 30% by weight, based on the total solid content. By making it 15% by weight or more, it is possible to sufficiently reduce the minimum reflectance and ensure sufficient total light transmittance, and by making it 35% by weight or less, it is possible to ensure sufficient scratch resistance.

[0027] The alumina fine particles (C) used in the present invention are blended for the purpose of increasing the hardness of the cured layer and improving the abrasion resistance. The primary average particle size of (C) is preferably 1 to 100 nm, more preferably 5 to 50 nm, and particularly preferably 10 to 30 nm. By making it 1 nm or more, it is possible to expect improvement in abrasion resistance, and by making it 100 nm or less, it is possible to ensure sufficient total light transmittance without increasing haze.

[0028] The amount of (C) in the low refractive index resin is preferably 2.0 to 10.0% by weight, more preferably 3.0 to 8.0% by weight, based on the total solid content. By making it 2.0% by weight or more, sufficient abrasion resistance can be ensured, and by making it 10.0% by weight or less, the reflectance can be kept sufficiently low. An example of a commercially available product is ALMIBK30WT%-M47 (product name: manufactured by CIK Nanotech Co., Ltd., solid content 30%, average particle size 20 nm).

[0029] The surface conditioner (D) used in the present invention is blended for the purpose of improving the leveling properties during coating, improving the slip properties of the cured layer to improve abrasion resistance, and further increasing water and oil repellency to improve antifouling properties. Blending (D) also makes it possible to suppress whitening (increase in haze) during stretching. It is preferable that the surface conditioner has a reactive functional group capable of polymerizing with a binder resin to form a cured coating film, in that the cured film does not fall off over time due to bleeding or the like, and the weather resistance effect can be maintained for a long period of time.

[0030] Examples of (D) include fluorine-based, silicone-based, and fluorine silicone-based compounds, which can be used alone or in combination of two or more. Among these, fluorine-based compounds are preferred because they have low surface free energy and tend to segregate on the coating film surface after coating and drying, and fluorine-based silicone compounds are particularly preferred because they can stabilize abrasion resistance and antifouling properties for a long period of time.

[0031] The amount of (D) in the low refractive index resin is preferably 20 to 45% by weight, more preferably 25 to 40% by weight, and particularly preferably 30 to 38% by weight, based on the total solid content. By making it 20% by weight or more, it is expected that whitening during stretching can be suppressed and that abrasion resistance and stain resistance can be improved, and by making it 45% by weight or less, sufficient curing properties can be ensured. An example of a commercially available product is X-71-1203M (trade name: manufactured by Shin-Etsu Chemical Co., Ltd., solid content 20%, fluorine-based silicone compound having reactive functional groups).

[0032] The photopolymerization initiator (E) used in the present invention generates radicals when irradiated with ultraviolet light or an electron beam, and the radicals trigger a polymerization reaction, and general-purpose photopolymerization initiators such as benzyl ketal, acetophenone, and phosphine oxide photopolymerization initiators can be used. By arbitrarily selecting the light absorption wavelength of the polymerization initiator, it is possible to impart curability over a wide wavelength range from the ultraviolet region to the visible light region. Specifically, benzyl ketals include 2,2-dimethoxy-1,2-diphenylethan-1-one, α-hydroxyacetophenones include 1-hydroxy-cyclohexyl-phenyl-ketone and 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, α-aminoacetophenones include 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, and acylphosphine oxides include 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, which may be used alone or in combination of two or more.

[0033] Among these, it is preferable to use an α-hydroxyacetophenone type which is less prone to yellowing, and Omnirad127D (2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]-phenyl}-2-methyl-propan-1-one) is particularly preferable because it is less susceptible to polymerization inhibition by oxygen. The amount of (E) to be blended per 100 parts by weight of the photopolymerizable component is preferably 3 to 15 parts by weight, more preferably 5 to 10 parts by weight.

[0034] To the low refractive index resin of the present invention, reactive diluents, ultraviolet absorbers, adhesion promoters, antioxidants, bluing agents, pigments, defoamers, precipitation inhibitors, antistatic agents, antifogging agents, antibacterial agents, waxes, matting agents, organic fine particles, etc. may be added as necessary within a range that does not impair the performance.

[0035] The reactive diluent is preferably a (meth)acrylate monomer having less than 6 functionalities. For example, butyl (meth)acrylate, isobornyl (meth)acrylate, hydroxyethyl (meth)acrylate, (poly)ethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, diglycerin tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, etc. can be used alone or in combination of two or more. The blending ratio of the reactive diluent is preferably 20% by weight or less, more preferably 5% by weight or less, based on the total solid content.

[0036] The low-refractive layer of the present invention can be laminated on the HC layer laminated on the light-transmitting substrate film to form an anti-reflection film. The HC resin for forming the HC layer is not particularly limited, but it is preferable to include a multifunctional urethane (meth)acrylate (hereinafter, a multifunctional ureac) as a binder, since it has a good balance between stretchability and abrasion resistance. As a commercially available product with particularly excellent moldability, Z-607-33 (trade name: manufactured by Aica Kogyo Co., Ltd., an HC agent containing 6-functional ureac) can be mentioned.

[0037] When the HC resin and the low refractive index resin are applied to a transparent support, they may be diluted with a solvent to improve the coating properties. Examples of dilution solvents include alcohol-based solvents such as ethanol, n-propyl alcohol, isopropyl alcohol (hereinafter referred to as IPA), n-butyl alcohol, isobutyl alcohol, and diacetone alcohol, ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone (hereinafter referred to as MIBK), and cyclohexanone, ester-based solvents such as ethyl acetate and butyl acetate, and ether-based solvents such as PGM, diethyl ether, and diisopropyl ether, which may be used alone or in combination of two or more.

[0038] The solid content when diluted is not particularly specified, and can be appropriately set so as to have a viscosity that is easy to apply. In the case of HC resin, the solid content is 10 to 50% by weight, and a mixed solvent of butyl acetate and PGM is preferable because it has a good balance between volatility and compatibility and can form a film with good appearance. In the case of low refractive index resin, the solid content is 0.5 to 10% by weight, and MIBK is preferable because it has a good balance between volatility and compatibility and can form a film with good appearance.

[0039] Examples of the light-transmitting substrate film to which the HC resin is applied include polyester film, triacetyl cellulose film, polycarbonate (hereinafter referred to as PC) film, polysulfone film, nylon film, cycloolefin film, acrylic (hereinafter referred to as PMMA) film, polyimide film, ABS film, polyolefin film, PVC film, PVA film, etc. Among these, biaxially stretched polyester film is preferably used from the viewpoints of weather resistance, processability, dimensional stability, etc. Furthermore, PMMA film, PC film, and laminated film thereof are preferably used for automobile decoration. The thickness of the film may be about 20 μm to 500 μm.

[0040] In order to improve adhesion to the HC resin, the base film may be subjected to a surface treatment such as a primer treatment, a sandblasting method, a solvent treatment, or the like to create a rough surface, or a surface oxidation treatment such as a corona discharge treatment, a chromic acid treatment, or an ozone / ultraviolet light irradiation treatment.

[0041] The method for applying the HC resin and the low refractive index resin is not particularly limited, and the resin can be formed by a known coating method such as spray coating, roll coating, die coating, air knife coating, blade coating, spin coating, reverse coating, gravure coating, or wire bar coating, or a printing method such as gravure printing, screen printing, offset printing, or inkjet printing.

[0042] The thickness of the HC resin layer when dry can be 1 μm to 10 μm, but is not limited thereto. The thickness of the low refractive resin layer applied on the HC resin layer when dry is preferably 50 to 200 nm, more preferably 80 to 150 nm. If the thickness of the low refractive layer is within this range, it is possible to sufficiently reduce the reflectance.

[0043] The light source of ultraviolet light used to cure HC resin and low bending resin includes low pressure mercury lamp, high pressure mercury lamp, extra high pressure mercury lamp, carbon arc lamp, xenon lamp, metal halide lamp, LED lamp, electrodeless ultraviolet lamp, etc., and the atmosphere for irradiation may be air or an inert gas such as nitrogen or argon. In addition, the curing property can be further improved by heating the back roll or the coating film with an IR heater during ultraviolet irradiation. The irradiation condition is an irradiation intensity of 500mW / cm. 2 ~3000mW / cm 2 , exposure dose 50-400mJ / cm 2 are given as examples, but are not limited to these.

[0044] The antireflection film of the present invention preferably has a breaking elongation of 100% or more, more preferably 200% or more, in an atmosphere at 130° C. If the breaking elongation is less than 100%, cracks may occur during molding in applications involving deep drawing.

[0045] The antireflection film of the present invention preferably has a haze of 0.5 or less, more preferably 0.3 or less, when stretched 100% in an atmosphere at 130° C. If the haze during stretching exceeds 0.5, the color of the decorative layer may change after molding, resulting in a subtle difference in appearance.

[0046] The antireflection film of the present invention preferably has a water contact angle of 100° or more, more preferably 110° or more. If the water contact angle is less than 100°, the antifouling properties may feel insufficient during use.

[0047] The present invention will be described in detail below with reference to examples and comparative examples, but these are illustrative and are not intended to be limiting. Unless otherwise specified, measurements were performed at room temperature of 25°C and relative humidity of 65%. The units in the recipe table are parts by weight. EXAMPLES

[0048] Preparation of urethane (meth)acrylate (hereinafter referred to as ureac) 1 200 parts by weight of ethylene glycol (hereinafter referred to as EG) and 922 parts by weight of IPDI (manufactured by Sumika Bayer Urethane Co., Ltd., product name Desmodur I, NCO group 37.5%) were added together with a catalyst to MEK solvent (solid content 60%) and stirred and reacted for 30 minutes at 30°C. The reaction was terminated when the peak of the isocyanate group reached a specified amount by infrared absorption analysis. Next, 400 parts by weight of PETA (manufactured by Nippon Kayaku Co., Ltd., product name PET30, solid content 100%) was added and stirred and reacted for 30 minutes at 10°C, and then stirred and reacted for 30 minutes at 60°C. The disappearance of the isocyanate group was confirmed by infrared absorption analysis, and the solid content was adjusted to 60% with MEK to obtain 6-functional ureac 1 with Mw.4,200.

[0049] Preparation of ureac 2 200 parts by weight of ethylene glycol (hereinafter referred to as EG) and 798 parts by weight of IPDI (manufactured by Sumika Bayer Urethane Co., Ltd., product name Desmodur I, NCO group 37.5%) were added together with a catalyst to MEK solvent (solid content 40%) and stirred and reacted for 30 minutes at 30°C. The reaction was terminated when the peak of the isocyanate group reached a specified amount by infrared absorption analysis. Next, 150 parts by weight of PETA (manufactured by Nippon Kayaku Co., Ltd., product name PET30, solid content 100%) was added and stirred and reacted for 30 minutes at 10°C, and then stirred and reacted for 30 minutes at 60°C. The disappearance of the isocyanate group was confirmed by infrared absorption analysis, and the solid content was adjusted to 60% with MEK to obtain 6-functional ureac 2 with Mw.8,000.

[0050] A ureac having the following structure was obtained by reaction according to known methods: Ureac 3: PETA-HDI-PETA structure, 6 functional groups, 100% solids Ureac 4: PETA-IPDI-PETA structure, 6 functional groups, 100% solids Ureac 5: HDI isocyanurate (※1)-PETA structure, 9 functional groups, 100% solids Urea A: DPPA(※2)-HDI-DPPA structure, 10 functional groups, 100% solids Urea B: HDI isocyanurate-DPPA skeleton, 15 functional groups, 100% solids (※1) There are three reactive bond points between isocyanurate and acrylate. (※2) Dipentaerythritol pentaacrylate.

[0051] Examples 1 to 6 The (a1) Ureacs 1-2 (6 functional, 60% solids) were used as the (a2), Ureacs 3-4 (6 functional, 100% solids) and Ureacs 5 (9 functional, 100% solids) were used as the (B), Sururia 4320 (trade name: manufactured by JGC Catalysts and Chemicals, 20% solids, primary average particle size 60 nm) was used as the (B), ALMIBK30WT%-M47 (trade name: manufactured by CIK Nanotech, 30% solids, average particle size 20 nm) was used as the (C), X-71-1203M (trade name: manufactured by Shin-Etsu Chemical, 20% solids, fluorine-based silicone compound having reactive functional groups) was used as the (D), and Omnirad127D (trade name: manufactured by IGM Resins) was used as the (E), and these were mixed as shown in Table 1, and further diluted with MIBK to a solid content of 1.5% by weight, and stirred until uniformly dissolved and dispersed to obtain the resin compositions of Examples 1-6.

[0052] Comparative Examples 1 to 8 In addition to the materials used in the examples, UreaC A (10 functional, 100% solids), UreaC B (15 functional, 100% solids) and KAYARAD DPHA (product name: Nippon Kayaku Co., Ltd., a mixture of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate) were used as binders and mixed as shown in Table 2. The mixture was then diluted with MIBK to a solid content of 1.5% by weight and stirred until uniformly dissolved and dispersed, obtaining the resin compositions of Comparative Examples 1 to 8.

[0053] Table 1 JPEG2025011388000001.jpg126145

[0054] Table 2 JPEG2025011388000002.jpg91129

[0055] The evaluation method was as follows.

[0056] Creating HC Film Using Z-607-33 (product name: Aica Kogyo Co., Ltd., molding hard coat agent containing hexafunctional ureac) as the HC agent, a photocurable resin was applied to the PMMA surface of PMMA / PC film C003 (product name: Sumitomo Chemical Co., Ltd., thickness 300 μm) so that the dry film thickness was 3.0 μm, and then dried at 80 °C for 1 minute, and then exposed to a high-pressure mercury lamp with an output of 1300 mW / cm 2 The coating was cured under conditions of an accumulated light quantity of 200 mJ to produce an HC film.

[0057] Creating anti-reflective film The low refractive index resin compositions in Tables 1 and 2 were applied onto the HC layer prepared above so that the film thickness after drying was 100 nm. After drying at 80°C for 1 minute, the film was exposed to a high pressure mercury lamp with an output of 1300 mW / cm in a nitrogen atmosphere. 2 The coating was cured under conditions of an accumulated light amount of 200 mJ to form an anti-reflection film.

[0058] Total light transmittance: The antireflection film was measured in accordance with JIS K7361-1 using a haze meter Haze-GARD2 manufactured by Toyo Seiki Seisakusho, and 92% or more was rated as ◯, and less than 92% was rated as x.

[0059] Haze: The anti-reflection film was measured using a haze meter Haze-GARD2 manufactured by Toyo Seiki Seisakusho in accordance with JIS K7136. A haze of 0.5% or less was evaluated as ◯, and a haze of more than 0.5% was evaluated as x.

[0060] Minimum reflectance: The surface opposite the coated surface was scratched with sandpaper, covered with a black pigment marker, and then black PET was attached to set the reflectance of the opposite surface to 0%. The reflectance of the HC surface was then plotted in 1 nm increments in the range of 380 nm to 780 nm using a spectrophotometer to measure the minimum reflectance. Reflectance of less than 1.5% was marked with ◎, 1.5 to 2.0% was marked with ◯, and over 2.0% was marked with ×.

[0061] Formability: The anti-reflective film was cut to 25 mm wide x 110 mm long, and a tensile test was performed using Minebea TechnoGraph TGI-1KN, with a chuck distance of 50 mm, an atmospheric temperature of 130°C, and a tensile speed of 300 mm / min. Cracks were visually confirmed, and the evaluation was performed with an elongation rate of 100% or more as ◯, and less than 100% as ×. Calculation formula: Calculate how many mm it has stretched based on 50 mm as the base. Stretched length (mm) / 50mm x 100 = stretch rate %

[0062] Haze (when stretched): The anti-reflection film was cut to 25 mm wide x 110 mm long, and stretched to an elongation of 100% using Minebea's TechnoGraph TGI-1KN, with a chuck distance of 50 mm, an atmospheric temperature of 130°C, and a pulling speed of 300 mm / min. The haze was then measured in the same manner as above, with less than 0.30% being rated as ◎, 0.3 to 0.50% being 〇, and over 0.50% being ×.

[0063] Abrasion resistance: Using a friction tester FR-IBS made by Suga Test Instruments, a friction element (diameter 16 mm) equipped with a test white cotton cloth (Kanakin No. 3) was used to rub the resin composition-coated surface of the anti-reflective film back and forth 100 mm at a speed of 1 back and forth per second under a load of 9 N. The appearance after 1,000 back and forth was confirmed, and a rating of ◯ was given if the anti-reflective layer did not peel off, and a rating of × if peeling occurred.

[0064] Water contact angle: In accordance with the sessile drop method of JIS R 3257:1999, using a DMs-400 manufactured by Kyowa Interface Science Co., Ltd., water was dropped onto samples in their normal state and after boiling for 1 hour at room temperature, and the contact angle was measured after leaving them to stand for 30 seconds. A value of 100° or more was marked as ◯, and a value of less than 100° was marked as ×.

[0065] Stain resistance: A continuous arc was drawn using an oil-based marker, Mackie Care Ultra Fine Point (product name: manufactured by Zebra), and then immediately wiped off with a cloth. If the mark was completely wiped off, it was marked as ◯, and if any part was left behind, it was marked as ×.

[0066] Evaluation results Table 3 JPEG2025011388000003.jpg180153

[0067] Table 4 JPEG2025011388000004.jpg159170

[0068] The examples were satisfactory with no problems in all respects, including total light transmittance, haze, minimum reflectance, moldability, haze (when stretched), abrasion resistance, water contact angle, and stain resistance.

[0069] On the other hand, Comparative Example 1, which used a monomer instead of (a2), had high haze when stretched, Comparative Example 2, which did not contain (a2), had poor abrasion resistance and antifouling properties, and Comparative Example 3, which did not contain (a1), had high haze when stretched. Comparative Example 4, which did not contain (B), had high minimum reflectance and low total light transmittance, and Comparative Example 5, which did not contain (C), had low abrasion resistance. Furthermore, Comparative Example 6, which did not contain (D), was poor in haze, abrasion resistance, water contact angle, and antifouling properties when stretched, and Comparative Examples 7 and 8, which were different in (a2), had high haze when stretched, and none of them were suitable for the present invention.

Claims

1. An anti-reflection film comprising a hard coat layer and a low refractive index layer laminated in this order on a light-transmitting substrate film, the low refractive index layer being a cured product of a low refractive index resin composition comprising a urethane (meth)acrylate (A), hollow silica (B), alumina fine particles (C), a surface conditioner (D), and a photopolymerization initiator (E), the (A) comprising a urethane acrylate (a1) having a structure obtained by reacting ethylene glycol with isophorone diisocyanate to form a diisocyanate, and further reacting pentaerythritol triacrylate with the diisocyanate, and a urethane (meth)acrylate (a2) having 9 or less functionalities (excluding (a1)).

2. 2. The anti-reflection film according to claim 1, wherein the blending amount of said (D) is 20 to 45% by weight based on the total solid content of the composition.

3. 2. The anti-reflection film according to claim 1, wherein the blending ratio of (a1) in (A) is 15 to 35% by weight based on the total solid content of (A).

4. 4. The anti-reflection film according to claim 1, which is a film for molding.

5. A molded product produced by using the anti-reflection film according to claim 4.

Citation Information

Patent Citations

  • JP1973048200A

Cited By

  • Low refractive index resin composition, anti-reflective film, and image display equipment and electronic equipment using the same.

    JP7932634B1